Towards the development of a larval feeding strategy for the white-margined sole (Dagetichthys marginatus) - Thompson, Ernst Frederick (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2014)
The major bottleneck during the domestication of the white-margined sole Dagetichthys marginatus in South Africa has been low larval survival. The cause of this is not clear but considering current literature on flatfish culture and more specifically soleid culture, nutritional deficiencies are hypothesized to be the main possible cause. Following the importance of nutrition, the first aim of the research was to use an ontogenetic developmental approach to develop a species specific larval feeding strategy. Ontogenetic development of D. marginatus showed that weaning will take place at much later ages than other soleids currently being farmed. This makes the partial replacement of Artemia with a suitable inert diet in co-feeding strategies very important to cut the cost associated of live food production. This leads on to the second aim, in which an 'in vitro' approach was used to model the digestibility of Artemia, which could ultimately contribute towards designing inert feeds with similar digestibility characteristics to Artemia in the future. Obtaining nutrients from food is closely linked to the functional status of the digestive tract, the support organs and the external morphological characteristics required for the ingestion of live or inert feeds. Considering both morphological and physiological ontogenetic development, it is clear that D. marginatus follow a similar pattern to other soleids. Larvae can successfully feed on Artemia as early as 3 days after hatching but exhibit a slow metamorphosis into the juvenile stage when compared to other soleids. The absence of any detectable acidic protease activity during the first 45 days of development and the importance of exogenous enzymes from Artemia all points to limited capacity to digest artificial diets. Prior to modelling the 'in vitro' digestion of Artemia, digestive enzyme activity at different pH's were modelled using functional forms from the normal distributive category of functions.,As there is no substantiated information for the general effects of pH on enzyme activity in the literature for finfish larvae, three species occurring in the same bio-geographical region of Dagetichthys marginatus, namely Sarpa salpa, Diplodus sargus capensis and Argyrosomus japonicus were used to investigate this effect. The fitted parameters, namely the optimal pH and sigma (the slope around the optimal pH) showed two interesting results. When using a negative log likelihood ratio test to test for differences between species for a particular enzyme, the optimal pH for alkaline proteases (7.67), lipase (8.03), amylase (7.69) and phosphatase (9.84) activity was the same for all three species. Furthermore, the study illustrated the potential to detect dietary shifts during ontogenetic development based on changes in enzyme activity around the optimal pH using the sigma parameter. Sarpa salpa showed increased amylase activity and a decrease in protease activity around the optimal pH with increased size, corresponding to a change in diet from zooplankton to algae. The 'in vitro' modelling approach taken in this study was based on known enzyme interactions and dynamics which makes the results very interpretable. from Artemia is achieved based on gut evacuation time and enzyme levels. This 'in vitro' study furthermore clearly indicates the importance of exogenous enzymes from Artemia, contributing as much as 54 percent to protein digestion and 64 "“ 72 percent to carbohydrate digestion. This was however, only an initial investigation, and further expansion of the model is required to achieve a complete understanding of Artemia digestion and ultimately partial replacement with artificial diets. A feeding strategy for D. marginatus should therefore follow those of other farmed soleids, although there will be a general delay in implementation due to slower development. Problems can thus be solved and improvements made by transferring technology from other soleids to D. marginatus.
Keywords: Flatfishes -- South Africa; Soleidae -- South Africa; Soleidae -- Larvae; Soleidae -- Larvae -- Feeding and feeds; Soleidae -- Larvae -- Physiology; Artemia